Locking Plates on Femoral Fractures: A Narrative Literature Review - Satria Putra Wicaksana (Open Access Indonesian Journal of Medical Reviews, 2021)
Plate fixation is still the most preferred method in treating distal femoral fractures. This literature review aimed to describe the locking plates on femoral fractures. Management of proximal humerus fractures remains a difficult problem for the orthopedic surgeon. In the setting of displaced fractures, there is no consensus on the best treatment option, with some studies favoring prosthetic replacement and others favoring reduction and plate fixation. The heterogeneity of multiple factors in the literature, including patient population, fracture type, and outcome measures reported, makes it difficult to determine the best treatment option for a given fracture pattern. Avascular necrosis is one of the most severe complications following open reduction internal fixation of proximal humerus fractures. In conclusion, the fixation of proximal humerus fractures with fixed-angle locking plates is a relatively new advancement in the field of orthopedics that has rapidly increased in popularity. Despite promising clinical results, there remains a high rate of complications that require further surgery, suggesting that the surgical technique should be used carefully and only in well-selected patients.